Investigation of the "central vein sign" in infratentorial multiple sclerosis lesions - Weber, Claudia Ellen; Sandikci, Vesile; Ebert, Anne; Szabo, Kristina; Platten, Michael; Gass, Achim; Eisele, Philipp (Multiple Sclerosis and Related Disorders, 2020)
Background - Recently there has been an increasing interest in the “central vein sign” (CVS) in multiple sclerosis (MS) lesions. Infratentorial brain regions represent typical predilection sites for MS lesion development and are part of the current McDonald criteria to demonstrate dissemination in space, but only a few studies investigated the presence of the CVS in infratentorial MS lesions. The aim of this study was to investigate the CVS in infratentorial MS lesions. - Methods - 3T MRI data sets from 119 patients with relapsing MS were analysed. Chronic lesions were identified on T2-weighted images. Co-registered T2 / susceptibility-weighted images (SWI) were analysed for the presence of the CVS. - Results - A total of 527 lesions were analysed. A CVS was present in the majority of infratentorial lesions (62/88, 70%). There was no difference in the frequencies of the CVS of infratentorial lesions compared to paraventricular lesions (67/81, 83%; p = 0.06) or subcortical (150/209; 72%; p = 0.82) lesions. Infratentorial lesions showed a CVS more often than juxtacortical lesions (16/34; 47%; p = 0.02), while periventricular lesions showed a CVS more often than infratentorial lesions (97/115; 84%, p = 0.02). - Conclusion - CVS is a frequent finding in infratentorial MS lesions that may increase the diagnostic value in MS.
Gesehen am 21.07.2025